Educational Interactive Video Content as a Media Contemporary Learning for Physical Education Teachers - Adi S; Tommy Soenyoto; Agus Darmawan; Hermawan Pamot Raharjo; Wahyu Arbanisa; Immanuel Berli Septian; Melinda Nur Aini; Ngatinah (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Teachers still need to gain an understanding of audio-visual-based learning media. How to make learning media, especially interactive videos. Teachers need to develop skills in creating and developing interactive learning videos that support learning activities. This training combines expository methods, demonstrations, and independent practice. This community service activity is carried out to provide training and experience through socialization and a direct approach to elementary school Physical Education teachers. This activity is carried out to increase teachers' knowledge and skills regarding learning media, in this case, interactive learning videos. Besides feeling the benefits of the action, the teachers hope there will be similar follow-up activities, such as training in making learning evaluations with google forms, training in making learning videos and optimizing the making of broadcast materials for learning materials.